ANALISIS PREDIKSI PENJUALAN IKLAN MEDIA MASA DAN ELEKTRONIK MENGGUNAKAN METODE LINEAR REGRESSION - Adham Novalas Putra Wibisono; Nuril Lutvi Azizah; Yunianita Rahmawati (Politeknik Bisnis Indonesia, 2024)
Technology continues to evolve rapidly, especially in the field of data analysis. Advertising sales in print and electronic media are one of the main strategies to achieve profits. In the context of today's era, successful ad sales require accurate and valid data. Linear Regression (LR) is a data analysis technique that predicts the value of unknown data by using other related and known data values. Mathematically model unknown or dependent variables and known or independent variables as linear equations. The research